(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To identify factors associated with the outcomes of benign prostatic hyperplasia using bipolar transurethral enucleation at 108 Military Central Hospital from 2024 to 2025. Methods: A prospective, longitudinal descriptive study was conducted on a case series of 68 patients with benign prostatic hyperplasia who underwent bipolar transurethral enucleation. Results: The mean operative time was 54.2±17.5 minutes, with a median of 50 minutes (IQR 40-65). Analysis revealed that factors significantly associated with operative time included preoperative prostate volume (p<0.001) and prostate morphology (p<0.001). There were 7 cases of intraoperative complications, accounting for 10.3% of the cohort. The analysis found no statistically significant association between intraoperative complications and patient characteristics such as age, comorbidities, preoperative prostate volume, or operative time (p>0.05). Conclusion: Preoperative prostate volume is a major predictor of operative time. Additionally, a trilobar enlargement morphology increases the complexity and prolongs the surgical duration.